Question and Answers Forum

All Questions      Topic List

Geometry Questions

Previous in All Question      Next in All Question      

Previous in Geometry      Next in Geometry      

Question Number 195892 by AROUNAMoussa last updated on 12/Aug/23

Answered by mr W last updated on 13/Aug/23

1+(√((4+1)^2 −(4−1)^2 ))+(√((4+2)^2 −(4−2)^2 ))+2  =7+4(√2)

1+(4+1)2(41)2+(4+2)2(42)2+2=7+42

Commented by AROUNAMoussa last updated on 13/Aug/23

Merci mais je n′ai rien compris,veillez donner des detailles !

Mercimaisjenairiencompris,veillezdonnerdesdetailles!

Commented by mr W last updated on 13/Aug/23

Commented by mr W last updated on 13/Aug/23

length of rectangle =1+a+b+2  a^2 +(4−1)^2 =(4+1)^2    ⇒a=(√((4+1)^2 −(4−1)^2 ))=4  b^2 +(4−2)^2 =(4+2)^2    ⇒b=(√((4+2)^2 −(4−2)^2 ))=4(√2)

lengthofrectangle=1+a+b+2a2+(41)2=(4+1)2a=(4+1)2(41)2=4b2+(42)2=(4+2)2b=(4+2)2(42)2=42

Commented by AROUNAMoussa last updated on 14/Aug/23

Merci bcp Mr W !

MercibcpMrW!

Terms of Service

Privacy Policy

Contact: info@tinkutara.com